Immune-mediated cholangiopathies in children: the need to better understand the pathophysiology for finding the future possible treatment targets - Grama, Alina; Mititelu, Alexandra; Sîrbe, Claudia; Benţa, Gabriel; Pop, Tudor Lucian (Frontiers in Immunology, 2023)
Cholangiopathies are defined as focal or extensive damage of the bile ducts. According to the pathogenetic mechanism, it may be immune-mediated or due to genetic, infectious, toxic, vascular, and obstructive causes. Their chronic evolution is characterized by inflammation, obstruction of bile flow, cholangiocyte proliferation and the progression toward fibrosis and cirrhosis. Immune-mediated cholangiopathies comprise primary sclerosing cholangitis (PSC), autoimmune cholangitis and IgG4associated cholangitis in adults and biliary atresia (BA), neonatal sclerosing cholangitis (NSC) in children.This is a provisional file, not the final typeset article of the immune mechanisms and pathophysiology of BA, NSC and PSC will open new perspectives for future treatments and better methods of preventing severe evolution.